PENGEMBANGAN MODUL PEMBELAJARAN MENGIDENTIFIKASI DOKUMEN-DOKUMEN KANTOR PADA MATA DIKLAT MELAKUKAN PROSEDUR ADMINISTRASI UNTUK SISWA KELAS X PRODI ADMINISTRASI PERKANTORAN - TRI KUSUMAWARDANI, FEBRIANI (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2013)
ABSTRACT   Module is one of the materials used in the learning process. From the initial observation results obtained from the data in the form of modules made training teachers perform administrative procedures in SMK Negeri 1 Sooko. The module reads student worksheet (LKS). However, modules like student worksheets are considered as modules are used in training the eyes perform administrative procedures. This module development research conducted using 4-D model of development (Four-D Models). This module development research aims to determine the feasibility of the process of development and learning modules identify office documents on the eyes Administrative Procedure Conduct training for vocational school students of class X which is expected to produce modules that correspond to the 4-D model of development (Four-D Models). Based on the analysis of the obtained results of the feasibility of modules that can be seen from the analysis of the feasibility of modules derived from the average overall validation of the validator with a percentage of 89.12% and an average of limited testing with a percentage of 87.58%, so the value of the second The obtained average overall percentage of 88.35% with a very decent criteria.   Keywords: Development, Learning Module, Identifying Office documents.